LANGUAGE AS A WEAPON: THE PRAGMATIC FUNCTION OF POINTERS AND REFERENCES IN SUPER SUS IMPOSTOR COMMUNICATION STRATEGIES - Anisa Luthfia; Shina Bella Nareswara (LPPM UNISDA, 2026)
Online multiplayer games such as Super Sus have become new linguistic environments where persuasion, deception, and identity are enacted through digital communication. This study investigates the pragmatic use of pointing (deixis) and referring (reference) expressions by Impostor players in Super Sus. By applying Levinson’s (1983) deixis theory and Yule’s (1996) reference framework, the study examines how linguistic expressions function as strategic tools for manipulating attention and constructing credibility. Data were collected qualitatively from in-game text and voice interactions between June and August 2025. Findings indicate that Impostors use four main pragmatic strategies: (1) vague deixis to diffuse suspicion, (2) specific reference to target others, (3) spatial–temporal deixis to fabricate alibis, and (4) person deixis to align or disalign with player groups. These findings demonstrate that in Super Sus, language functions not merely as communication but as a weapon, an instrument of survival and deception in digital interaction.